CD40 Activation Rescues Antiviral CD8+ T Cells from PD-1-Mediated Exhaustion - Isogawa, Masanori; Chung, Josan; Murata, Yasuhiro; Kakimi, Kazuhiro; Chisari, Francis V. (PLoS pathogens, 2013)
The intrahepatic immune environment is normally biased towards tolerance. Nonetheless, effective antiviral immune responses can be induced against hepatotropic pathogens. To examine the immunological basis of this paradox we studied the ability of hepatocellularly expressed hepatitis B virus (HBV) to activate immunologically naïve HBV-specific CD8⁺ T cell receptor (TCR) transgenic T cells after adoptive transfer to HBV transgenic mice. Intrahepatic priming triggered vigorous in situ T cell proliferation but failed to induce interferon gamma production or cytolytic effector function. In contrast, the same T cells differentiated into cytolytic effector T cells in HBV transgenic mice if Programmed Death 1 (PD-1) expression was genetically ablated, suggesting that intrahepatic antigen presentation per se triggers negative regulatory signals that prevent the functional differentiation of naïve CD8⁺ T cells. Surprisingly, coadministration of an agonistic anti-CD40 antibody (αCD40) inhibited PD-1 induction and restored T cell effector function, thereby inhibiting viral gene expression and causing a necroinflammatory liver disease. Importantly, the depletion of myeloid dendritic cells (mDCs) strongly diminished the αCD40 mediated functional differentiation of HBV-specific CD8⁺ T cells, suggesting that activation of mDCs was responsible for the functional differentiation of HBV-specific CD8⁺ T cells in αCD40 treated animals. These results demonstrate that antigen-specific, PD-1-mediated CD8⁺ T cell exhaustion can be rescued by CD40-mediated mDC-activation.